Geography of Bangladesh - Rashid, Harun Er (Dhaka : university Press Limited, 1991)
Environment Management
Keywords: Geography; Physical feature; Hydrography; Climate; Soil; Forests; Land; Agriculture; Animal husbandry; Fisheries; Transport; Communication; Industries; Natural resources; Trade; Population; Economic framework; Development planning; Environmental issues